PENGARUH NILAI PERUSAHAAN, LEVERAGE, DAN MEDIA EXPOSURE TERHADAP CARBON EMISSION DISCLOSURE - Syahida Ayu Laksani (2020)
This study aims to examine the effect of firm value, leverage, and media exposure on carbon emissions disclosure. Firm value is measured by Tobin's Q, leverage is measured using a debt to assets ratio, media exposure is a dummy variable with company that disclose more information related to carbon emissions through online media that are disclosed by external parties given 1, while 0 if vice versa. Variable carbon emissions disclosure was measured based on 18 disclosure checklist items developed by Bae Choi et al. (2013). This research was conducted on non-financial sector companies listed on the Indonesia Stock Exchange during the 2015-2018 period. Samples were selected based on purposive sampling, so as many as 23 companies were collected per year of research samples. With the hypothesis test that is multiple linear regression analysis using the SPSS program. This study shows that firm value and media exposure do not significantly influence the disclosure of carbon emissions. While leverage has a significant negative effect on disclosure of carbon emissions, where companies with high leverage will be more likely not to disclose the carbon emissions information.